Analysis/Spectrum of admitted cases of lower extremity arterial disease (LEAD) in University Hospital of Nepal - karmacharya, Robin Man; Vaidya, Satish; Singh, Amit Kumar; Dhakal, Prasesh; Dahal, Sushil; Shrestha, Prabha; Bade, Sohail; Bhandari, Niroj (Annapurna Journal of Health Sciences, 2023)
Introduction: Peripheral arterial disease is a condition due to partial or complete occlusion of arteries excluding that of heart and brain. Lower extremity arterial disease is specific to lower limbs. Some of the patients are asymptomatic while a majority present with claudication, rest pain, ulceration or even gangrene. Methods: We took all admitted cases of lower extremity arterial disease from January, 2015 to December 2018. ABI was used as the first clinical tool for the diagnosis of PAD in patients with history or physical examination findings suggestive of PAD as per AHA guidelines. Outpatient arterial Doppler ultrasonography complemented by lower limb CT angiogram was used as a confirmatory tool for the diagnosis and also to assess anatomical location and severity of stenosis. Results: Total of 54 cases of lower extremity arterial diseases were identified with a mean age of 59.2 years (S.D. 11.4). Right lower limb was involved in 35(50%). Mean age was 58 years(SD 13.1). Mean duration of symptom was 3.4 years (SD 3.3). Claudication was present in all the patients. 32(45.7%) had ulcers. Toe(44.3%) was most commonly involved. Decreased local temperature(91.4%) and color change(87.1%) were major symptoms. 35(50%) of the patients had gangrene. Mean peak systolic velocity was lowest in the peroneal artery. 16.6% patients got additional peripheral bypass surgery. Conclusion: Claudication, decreased local temperature and color change were very common findings of lower extremity arterial disease. Gangrene was present in half of the patients.